1998
DOI: 10.1172/jci4238
|View full text |Cite
|
Sign up to set email alerts
|

Autoreactive T cells to platelet GPIIb-IIIa in immune thrombocytopenic purpura. Role in production of anti-platelet autoantibody.

Abstract: T cell proliferative responses to platelet membrane GPIIbIIIa were examined in 14 patients with chronic immune thrombocytopenic purpura (ITP), 7 systemic lupus erythematosus (SLE) patients with or without thrombocytopenia, and 10 healthy donors. Although peripheral blood T cells from all subjects failed to respond to the protein complex in its native state, reduced GPIIb-IIIa stimulated T cells from three ITP patients and one SLE patient with thrombocytopenia, and tryptic peptides of GPIIb-IIIa stimulated T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
176
1
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(186 citation statements)
references
References 43 publications
7
176
1
2
Order By: Relevance
“…However, Tcell mediated mechanisms independent from autoantibodies may also be involved (5). The presence of auto-reactive T cell clones against GPIIb/IIIa epitopes in patients with ITP were shown by Kuwana et al (19). Other studies have also shown the presence of cytotoxic T cells against autologous thrombocytes.…”
Section: Discussionmentioning
confidence: 94%
“…However, Tcell mediated mechanisms independent from autoantibodies may also be involved (5). The presence of auto-reactive T cell clones against GPIIb/IIIa epitopes in patients with ITP were shown by Kuwana et al (19). Other studies have also shown the presence of cytotoxic T cells against autologous thrombocytes.…”
Section: Discussionmentioning
confidence: 94%
“…This might be expected, as B cells are the ultimate producers of anti-platelet antibodies, and patients with ITP have an increased generation of antiplatelet antibodies [23]. The pathogenic B cells are stimulated by platelet-specific helper T cells to proliferate into autoantibody-secreting cells and thus they may be responsible for decreased peripheral blood platelet count in patients with ITP [24]. Rituximab, an anti-CD20 monoclonal antibody that depletes B cells, has been used to treat ITP for about a decade and has shown its efficacy in a subpopulation of ITP patients [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Support for the primary role of T cells in promoting specific autoantibody responses comes from work in other diseases such as scleroderma, systemic lupus erythematosus, anti-phospholipid Ab syndrome, and immune thrombocytopenic purpura (12)(13)(14)(15)(16)(17). Moreover, in the T cell-mediated autoimmune disease primary biliary cirrhosis, bile duct-infiltrating T cells and a subpopulation of peripheral blood CD4 ϩ T cells recognize the same Ag (pyruvate dehydrogenase complex) that is targeted by a highly stereotypical, but nonpathogenic, Ab response (18 -21).…”
Section: P Olymyositis (Pm)mentioning
confidence: 99%